The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1590/s1677-5538.ibju.2024.0039
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functional outcomes and surgical retreatment after thulium laser enucleation of the prostate: A 10-year follow-up study

Celeste Manfredi,
Luigi Napolitano,
Francesco Ditonno
et al.

Abstract: Background: To evaluate the 10-year functional outcomes (primary) and frequency and predictors of BPH surgical retreatment (secondary) after ThuLEP. Materials and Methods: A single-center retrospective analysis of consecutive patients undergoing ThuLEP between 2010 and 2013 was performed. Inclusion criteria were: age ≥ 40 years, prostate volume (PV) ≥ 80 mL, International Prostate Symptom Score (IPSS)-Total score ≥ 8 points. IPSS-Total score was the primary outcome, and BPH surgical retreatment rate was the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Dr. Manfredi and collegues from Italy performed in page 309 ( 5 ) a study about the new technologies in BPH treatment. The authors shows the long term functional outcomes and surgical retreatment after thulium laser enucleation of prostate and concluded that ThuLEP is associated with optimal functional outcomes and a low frequency of BPH surgical retreatment in the long-term.…”
mentioning
confidence: 99%
“…Dr. Manfredi and collegues from Italy performed in page 309 ( 5 ) a study about the new technologies in BPH treatment. The authors shows the long term functional outcomes and surgical retreatment after thulium laser enucleation of prostate and concluded that ThuLEP is associated with optimal functional outcomes and a low frequency of BPH surgical retreatment in the long-term.…”
mentioning
confidence: 99%